Ctenarytaina bipartita sp. n. (Hemiptera, Psylloidea), a new eucalypt psyllid from Southeast Australia - Burckhardt, Daniel; Farnier, Kevin; Queiroz, Dalva L.; Taylor, Gary S.; Steinbauer, Martin J. (Zootaxa, 2013)
Ctenarytaina bipartita sp.n., associated with Eucalyptus kitsoniana and E. viminalis, is described from the Australian Capital Territory, New South Wales, Tasmania and Victoria. It differs from other described Ctenarytaina species in the paramere which bears a small posterior lobe. Taxonomically relevant morphological details are illustrated and the species is diagnosed from other eucalypt inhabiting congeners. Information on the biology is also given. C. bipartita has the po-tential to become an exported pest species to countries with significant eucalypt plantations.